Menganalisis Kontribusi Pajak Dan Retribusi Dalam Perekonomian - Selvira Aryani; Wahjoe Pangestoeti; Sheilla Rosalina; Fazila Shafitri Ananda (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
This study aims to analyze the contribution of taxes and levies in a country's economy, focusing on the case of Indonesia. Taxes and user charges are fiscal policy instruments that play an important role in collecting government revenue to finance various development activities and public services. However, there are still various challenges in optimizing the contribution of these two instruments. The research method used is descriptive qualitative analysis, by conducting a literature review and case study of the tax and levy system in Indonesia. The results of the analysis show that taxes and user charges contribute significantly to the Indonesian economy, but there are problems such as low public tax awareness, potential tax leakage, and lack of transparency in the management of local user charges.